State Policy as an Element Of International Crimes - Schabas, William (2009)
This article addresses the use of state policy as an element that is part of the configuration of international crimes. To this end, the author analyses how international tribunals have understood the adoption of State policies in the commission of such crimes under international criminal law. The author also examines the concept of genocide and its link to the existence of a State plan or policy for its configuration; as well as the implications of adopting a broad concept of "State policies" that includes non-State actors in its approach, the figure of "the joint criminal enterprise" and the concept of gravity in these crimes with the aim of providing that the relevance of the plan or policy of State is reviewed in the configuration of international crimes.